SIT LESS: A prototype home-based system for monitoring older adults sedentary behavior. - Tirkel, Tzafit; Edan, Yael; Khvorostianov, Natalia; Bar-Haim, Simona (Assistive Technology, 2020)
This paper presents the overall design of a prototype home-based system aimed to reduce sedentary behavior of older adults. Quantitative performance indicators were developed to measure the sedentary behavior and daily activities of an older adult. The sedentary behavior is monitored by identifying individual positions (standing, sitting, and lying) within the field of view of a Microsoft Kinect sensor, using a custom designed algorithm. The physical activity of the older adult when outside the field of view of the Microsoft Kinect sensor is monitored by counting the number of steps using a Fitbit Charge HR watch, which the older adult is equipped with. A user interface was developed on a PC platform to interact with the older adult. The user interface is automatically operated and includes several modules. It displays the activity level, and provides feedbacks, alerts, and reminders to reduce sedentary behavior. Evaluations using a mixed methods approach that included a focus group, interviews, and observations were conducted to examine the integrated system, evaluate the users' experience with the system, and compare different types of feedbacks and alerts. The analyses indicated the feasibility of the proposed SIT LESS system along with recommendations for improving the system in future research.